Ethical Challenges Related to Patient Involvement in Health Technology Assessment. (28th June 2019) - Vanstone, Meredith; Abelson, Julia; Bidonde, Julia; Bond, Kenneth; Burgess, Raquel; Canfield, Carolyn; Schwartz, Lisa; Tripp, Laura
Abstract: Including information and values from patients in HTA has the potential to improve both the process and outcomes of health technology policy decisions. Accordingly, funding and structural incentives to include patients in HTA activities have increased over the past several years. Unfortunately, these incentives have not yet been accompanied by a corresponding increase in resources, time, or commitment to responsiveness. In this Perspectives piece, we reflect on our collective experiences participating in, conducting, and overseeing patient engagement activities within HTA to highlight the ethical challenges associated with this area of activity. While we remain committed to the idea that patient engagement activities strengthen the findings, relevance, and legitimacy of health technology policy, we are deeply concerned about the potential for these activities to do ethical harm. We use this analysis to call for action to introduce strong protections against ethical violations that may harm patients participating in HTA engagement activities.